Students’ Trust in AI Feedback and Its Effect on Critical Reading In EFL - Seva Silfia Andriani; Washlurachim Safitri; Kiagus Baluqiah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The use of artificial intelligence (AI) in English as a Foreign Language (EFL) instruction has increased, particularly through AI-generated feedback to support reading activities. However, research on students’ trust in AI feedback and its relationship with critical reading ability remains limited. This study investigates EFL students’ trust in AI-generated feedback and examines its relationship with critical reading performance. Using a quantitative correlational design, the study involved 17 undergraduate EFL students at Universitas Muhammadiyah Bengkulu, Indonesia. Data were collected through a five-item Likert-scale questionnaire measuring trust in AI feedback and a five-item critical reading test. Descriptive statistics and Spearman’s rank correlation analysis were applied. The results show that students demonstrated a moderate level of trust in AI-generated feedback (M = 3.40 per item) and moderate to relatively high critical reading performance (M = 3.35 out of 5). The correlation analysis revealed a positive but weak relationship between trust in AI feedback and critical reading performance (ρ = 0.28, p = .27), indicating no statistically significant correlation. These findings suggest that although students generally trust AI-generated feedback, such trust alone does not significantly enhance critical reading ability, highlighting the importance of integrating AI feedback with teacher guidance in EFL reading instruction.